Tetrodotoxin, fungal pathogen infection, and bacterial microbiome associations are variable in the skin microecosystems of two Taricha newt species - Talon Jost; Talon Jost; Alysha Henderson; Brandon LaBumbard; Krisztian Magori; Amber Stokes; Danica Bergin; Autumn Holley; Autumn Holley; Molly Bletz; Molly Bletz; Obed Hernández-Gómez; et al. (Frontiers in Amphibian and Reptile Science)
A diverse metabolome exists on amphibian skin that mediates interactions between hosts and skin microbiomes. Tetrodotoxin is one such metabolite that occurs across a variety of taxa, and is particularly well studied in newts of the genus Taricha that are susceptible to infection with chytrid fungi. The interaction of tetrodotoxin with the skin microbiome, including pathogenic fungi, is not well understood, and here we describe these patterns across 12 populations of Taricha granulosa and T. torosa in Washington, Oregon, and California. We found no correlation of TTX and Batrachochytrium dendrobatidis (Bd) infection in either T. granulosa or T. torosa, a pattern inconsistent with a previous study. In addition, TTX, but not Bd, was significantly correlated with the skin microbiome composition in T. granulosa. In T. torosa, however, Bd, but not TTX, was correlated with the skin microbiome structure. The relationship between TTX and skin microbiome composition differed between species, with significant correlations observed only in T. granulosa, which exhibited higher TTX concentrations. We also detected significantly higher abundances of bacterial taxa (e.g., Pseudomonadaceae) associated with TTX production in newts with higher skin TTX. These taxa (ASVs matching Aeromonas, Pseudomonas, Shewanella, and Sphingopyxis) were associated with all body sites of previously sampled T. granulosa, but not found in soil samples. Our results suggest that toxins can shape the newt skin microbiome and may influence pathogen infection through indirect mechanisms, as TTX showed no direct inhibition of Bd or B. salamandrivorans growth.